Philosophical Review on the Basic & Action Research Methods-A Critical Analysis - Pradeep M. D., (International Journal of Management, Technology and Social Sciences (IJMTS), 2018)
Research means searching for knowledge by utilizing appropriate scientific and systematic approach. It presumes the status of human voyage for the discovery by exploring ones inquisitive urge to gain knowledge over the unidentified aspects connected to life. Research aim to acquire new knowledge or expansion of existing information through some value additions. Varied forms of research methods are adopted to find appropriate solutions for diversified problems of the society. The decision on the application of Basic and Applied research can be better done on the scrutiny of nature of prevailing problem and its solutions. Knowledge domain would get stagnated unless new practical discoveries are conducted with the help of applied research. Even though all basic research will not lead to create new knowledge, it certainly helps to identify new application for conducting applied research on the existing problems by providing required tools and raw materials for the study intern deliver utilitarian benefits to the society. This study puts light on the implications of basic as well as applied research methodologies by reviewing into its evolution, features, steps, merits and demerits. It also tries to distinguish between basic research and applied research focusing upon its utility aspects.